Taking small steps towards targets – perspectives for clinical practice in diabetes, cardiometabolic disorders and beyond. Issue 4 (24th March 2013) - Golay, A.; Brock, E.; Gabriel, R.; Konrad, T.; Lalic, N.; Laville, M.; Mingrone, G.; Petrie, J.; Phan, T.‐M.; Pietiläinen, K. H.; Anderwald, C.‐H.
Summary Big changes are hard. When trying to achieve guideline targets in diabetes and cardiometabolic disorders, patients can lack commitment or suffer despondency. It is much easier to make small changes in lifestyle or treatment, which are less noticeable and easier to manage long‐term. Obesity is central to the cardiometabolic disorders, and even small weight losses of 2–5% can improve the cardiometabolic risk profile and substantially reduce the risk of developing type 2 diabetes. Likewise, small increases in physical activity, such as 15–30 min of brisk walking per day, can cut the risk of heart disease by 10%. Lifestyle or treatment changes that lead to small improvements in metabolic parameters also impact patient outcome – for example, a 5 mmHg decrease in blood pressure can translate into significant reductions in the rates of myocardial infarction and cardiovascular mortality. Benefits of small changes can also be seen in health economic outcome models. Implementing change at an individual versus a population level has different implications for overall benefit and patient motivation. Even very small steps taken in trying to reach guideline targets should represent a positive achievement for patients. Patient engagement is essential – only when patients commit themselves to change can benefits be maintained, and physicians should recognise their influence. Small changes in individual parameters can result in significant beneficial effects; however, a major impact can occur when small changes are made together in multiple parameters. More research is required to elucidate the full impact of small changes on patient outcome.